Study of COVID-19 pandemic in London (UK) from urban context. (November 2020) - Ghosh, Aritra; Nundy, Srijita; Ghosh, Sumedha; Mallick, Tapas K.
Abstract: COVID-19 transmission in London city was discussed in this work from an urban context. The association between COVID-19 cases and climate indicators in London, UK were analysed statistically employing published data from national health services, UK and Time and Date AS based weather data. The climatic indicators included in the study were the daily averages of maximum and minimum temperatures, humidity, and wind speed. Pearson, Kendall, and Spearman rank correlation tests were selected for data analysis. The data was considered up to two different dates to study the climatic effect (10th May in the first study and then updated up to 16th of July in the next study when the rest of the data was available). The results were contradictory in the two studies and it can be concluded that climatic parameters cannot solely determine the changes in the number of cases in the pandemic. Distance from London to four other cities (Birmingham, Leeds, Manchester, and Sheffield) showed that as the distance from the epicentre of the UK (London) increases, the number of COVID-19 cases decrease. What should be the necessary measure to be taken to control the transmission in cities have been discussed. Highlights: This study presents an investigation of the COVID-19 transmission from the urban context. Climatic data (temperature and humidity) is not a strong parameter to understand the transmission of COVID-19 pandemic. Distance from London to other cities was negatively associated with COVID-19 cases.